Energy and Sustainability IV 2013
DOI: 10.2495/esus130271
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of suspended particulate matter emitted from combustion of agricultural residue biomass under different temperatures

Abstract: There are large quantities of waste rice husk and straw estimated around 3.9 million tons as biomass waste every year in Japan. Air pollutants emitted from exhaust gases of rice husk incineration lead to environmental damage, not only because of the influence on global environment and climate, when released into the atmosphere, but also on human health due to local air pollution. Therefore, it is necessary to effectively utilize waste rice husk and straw to reduce air pollutants. In recent years, there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The emissions of low molecular weight organic acids also follow the similar variation trends with combustion efficiency as those of OC or WSOC emission factors ( Figure S2). These trends are generally in agreement with previous studies (Dhammapala et al, 2006;Holder et al, 2016;Jen et al, 2019;Reisen et al, 2018;Wang et al, 2013). Under the same burning conditions, the emission factors of particles or organic aerosols from corn burning were slightly higher than those from wheat burning (Figure 3).…”
Section: Influence Of Combustion Efficiency On Emission Factorssupporting
confidence: 92%
“…The emissions of low molecular weight organic acids also follow the similar variation trends with combustion efficiency as those of OC or WSOC emission factors ( Figure S2). These trends are generally in agreement with previous studies (Dhammapala et al, 2006;Holder et al, 2016;Jen et al, 2019;Reisen et al, 2018;Wang et al, 2013). Under the same burning conditions, the emission factors of particles or organic aerosols from corn burning were slightly higher than those from wheat burning (Figure 3).…”
Section: Influence Of Combustion Efficiency On Emission Factorssupporting
confidence: 92%
“…Since waste rice husk heating value is lower than waste rice straw based on our studies [10][11], however, waste rice husk and straw is much lower when compared to fossil fuel. Therefore, it is necessary to find the suitable combustion conditions for effective utilization as biomass fuel of waste rice husk.…”
Section: Measurements In the Composition Of Waste Rice Huskmentioning
confidence: 68%
“…It is worth to develop different technologies for controlling air pollutants emitted from fuel utilization. Some achievements in this study have been applied and linked with other studies reported during the 4th International Conference on Energy and Sustainability [17][18][19].…”
Section: Co 2 Gasifi Cation Reactivity Of Waste Wood Char Samplesmentioning
confidence: 71%